Pengaruh Gcg, Profitabilitas, Capital Intensity, dan Ukuran Perusahaan terhadap Tax Avoidance - Dian Eva Marlinda; Kartika Hendra Titisari; Endang Masitoh (Ekonomis: Journal of Economics and Business, 2020)
Tax Avoidance is a taxpayer's attempt to exploit the legal gap for the tax to be minimized. The study aims to empirically know the influence of good corporate governance (independent Board of Commissioners, institutional ownership, Audit Committee), profitability, capital intensity, and size of the company To the tax avoidance of the banking sector companies listed on the Indonesia Stock Exchange (IDX) with a 3-year observation period in 2016-2018. The theory used in this study was agency theory. The population in this research is the entire banking sector company listed on the Indonesia Stock Exchange period 2016-2018 with the determination of research samples using the purposive sampling method, resulting in a sample of 21 companies Banking sector. The data analysis techniques used in this study were multiple linear regression. The results of this research show that an independent board of Commissioners, profitability, and capital intensity do not affect tax avoidance. Meanwhile, institutional ownership, audit committee, and size affect tax avoidance.